Cytomegalovirus-Specific Immunoglobulin G Is Associated With Chronic Lung Disease in Children and Adolescents from Sub-Saharan Africa Living With Perinatal Human Immunodeficiency Virus. (26th November 2020) - Hameiri Bowen, Dan; Sovershaeva, Evgeniya; Charlton, Bethany; Schive, Cecilie; Odland, Jon; McHugh, Grace; Bandason, Tsitsi; Mayini, Justin; Ferrand, Rashida A; Yindom, Louis-Marie; Rowland-Jones, Sarah L
Abstract: In a cross-sectional study of 296 children and adolescents from Zimbabwe living with perinatal human immunodeficiency virus, individuals with the top tertile of cytomegalovirus-specific immunoglobulin G titer had an increased odds of chronic lung disease (odds ratio, 3.33; 95% confidence interval, 1.37–8.85; P = .010).